Dynamics for droplet-based electricity generators. (February 2021) - Wang, Xiang; Fang, Sunmiao; Tan, Jin; Hu, Tao; Chu, Weicun; Yin, Jun; Zhou, Jianxin; Guo, Wanlin
Abstract: The finding of power generation from droplets (Yin et al., 2014) [1], based on the moving boundary of electrical double layer, has triggered great research enthusiasm, and a breakthrough in instantaneous electric power density was achieved recently by a droplet-based electricity generator (DEG) (Xu et al., 2020) [2]. However, the dynamic mechanism for such droplet-based electricity generators remains elusive, impeding optimization of the DEGs for practical applications. Through comprehensive experiments, we developed a dynamic model of surface charge density that can explain the underlying mechanism for the DEGs. The spreading droplet in touch with the top electrode can be equivalently regarded as an additional part of the top electrode, and the change of droplet area causes the change of surface charge density of the top electrode, driving electrons to migrate between the two electrodes. The insight of the dynamic mechanism paves a way for optimal design and practical applications of the DEGs. Graphical Abstract: ga1 Highlights: Direct correspondence between the droplet-induced voltage signal and area change rate dS/dt of the droplet is revealed. A dynamic model based on experiments is proposed, which provides deep insights of the underlying mechanism for the DEGs. Variable impacts on the droplet-based electricity generator are quantitatively demonstrated.